Law Enforcement Againts Motorcyclist Violations (Case Study of Maros Police) - Astuty Sumanto, R.R. Eko Widy; Bima Muttaqin, Elfran; Juliansi Sandapang, Ismelly; Halik, Johannes Baptista (SocioHumania: Journal of Social Humanities Studies, 2024)
This study aims to determine the law enforcement of motorcycle driver traffic violations from 2020-2022 in the Maros police station and to find out efforts to overcome traffic violations against motorcycle drivers in the Maros police traffic unit. This research uses empirical juridical research methods, namely research procedures that produce descriptive data in the form of written words examining the theories of the concepts of legal principles as well as laws and regulations and oral from people. The types and sources of data used are primary data obtained directly in the field or research location at the Maros police station through interview techniques, secondary data traced through literature review either sourced form books, magazines, journals, or media. As for the results of this study, namely law enforcement of motorcycle driver traffic violations in Maros district, from research data violations committed by the Maros community every year continue to increase. The most common cases are not wearing an Indonesian national standard helmet (SNI) and not carrying documents in the form of a driver’s license (SIM) and vehicle registration number (STNK) when driving. One of the factors causing less than optimal law enforcement is due to the covid-19 pandemic. The countermeasures taken by the Maros police are, pre-emtif efforts in the form of socialization, preventive efforts in the form of obedient operations and repressive efforts in the form of giving ticket sanctions to violators.